Diversity of Rust Fungi with Special Emphasis on Hyalopsora erlangensis Causing Disease in Cystopteris chinensis - An Yu; Xia Zhao; Xiaohong Chen (Diversity)
A newly discovered rust fungus poses a significant threat to the survival and reproduction of the endangered plant Cystopteris chinensis in a forest in western Sichuan province, China. This study utilized both morphological analysis and molecular phylogenetic approaches to classify this fungal taxon. Artificial inoculation experiments, which involved sampling uredia from the field, were conducted to fulfill Koch’s postulates. Our results designate this rust fungus as a novel species within the Pucciniastraceae family, named Hyalopsora erlangensis A. Yu & X.H. Chen. Morphological features, including hyaline peridia cells, yellowish urediniospores, dark brown amphispores with three germ pores, and pigmented cytoplasm, differentiate this species from others in the genera Milesina, Uredinopsis, and Pucciniastrum. Phylogenetic analysis, based on internal transcribed spacer (ITS) sequences and 28S rDNA gene fragments, further confirms its distinctiveness from other Hyalopsora species, supported by high maximum parsimony (MP), maximum likelihood (ML), and Bayesian inference (BI) bootstrap values. Artificial inoculation both in the field and in tissue-cultured seedlings verified this fungus as the causative agent of C. chinensis rust disease. Our research not only identifies the pathogen but also offers fundamental insights for fern rust diversity, and the future management and conservation of this endangered fern, aiming to mitigate the impact of this devastating rust.